2022
DOI: 10.3389/fphar.2022.839305
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Xingnaojing Injection for Emergency Treatment of Acute Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: Background: Xingnaojing injection (XNJ) is derived from a traditional Chinese prescription named Angong Niuhuang pill. As an adjuvant treatment widely used in acute ischemic stroke (AIS), XNJ has proven to be effective with certain clinical evidence. The aim of this study is to collect the latest evidence and evaluate efficacy and safety of XNJ for emergency treatment of AIS.Methods: We searched seven literature databases and two clinical trial registries from their inception to November 14, 2021 for randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Traditional Chinese herbs have the advantages of being multicentric, multitargeted, holistically regulated, and having few side effects in the treatment of AIS ( Fan et al, 2020 ; Li et al, 2022b ; Ye et al, 2022 ) Several meta-analyses and systematic evaluations of proprietary herbal compound preparations have shown significant effects on the degree of neurological deficits, the speed of neurological recovery, and the ability to perform activities of daily living in patients with AIS ( Lyu et al, 2020a ; 2020b ; Liu et al, 2021 ; Tian et al, 2021 ; Wang et al, 2022c ). Recent pharmacological studies have found that Chinese herbal medicine can treat AIS through several mechanisms, including protecting neurological function, promoting microvascular regeneration, and improving energy metabolism in ischemic cells.…”
Section: Chinese Herbal Medicine For Ais Has Advantagesmentioning
confidence: 99%
“…Traditional Chinese herbs have the advantages of being multicentric, multitargeted, holistically regulated, and having few side effects in the treatment of AIS ( Fan et al, 2020 ; Li et al, 2022b ; Ye et al, 2022 ) Several meta-analyses and systematic evaluations of proprietary herbal compound preparations have shown significant effects on the degree of neurological deficits, the speed of neurological recovery, and the ability to perform activities of daily living in patients with AIS ( Lyu et al, 2020a ; 2020b ; Liu et al, 2021 ; Tian et al, 2021 ; Wang et al, 2022c ). Recent pharmacological studies have found that Chinese herbal medicine can treat AIS through several mechanisms, including protecting neurological function, promoting microvascular regeneration, and improving energy metabolism in ischemic cells.…”
Section: Chinese Herbal Medicine For Ais Has Advantagesmentioning
confidence: 99%
“…Baihu Decoction (BHD) is a type of herbal decoction that is used as an antipyretic medicine with the famous effects of removing heat and promoting the production of body fluids and was first recorded in the Shanghan Lun ( Treatise on Cold Damage Diseases ) ( Wang et al, 2022a ). BHD, also known as White Tiger Decoction, has been extensively used in the early stage of acute infection and inflammation.…”
Section: Herbal Formulas Of Tcm Against Hsmentioning
confidence: 99%
“…Xingnaojing injection (XNJ) is the only Chinese herbal injection approved for emergency treatment of stroke in China [ 130 ]. In the treatment of ischemic stroke, XNJ results in a significantly better overall response rate and better improvement of clinical symptoms than conventional treatment alone [ 130 , 131 ]. In addition, XNJ can be used alone or as an adjuvant therapy to reduce brain damage and improve nerve health for the treatment of acute cerebral hemorrhage [ 132 ] and traumatic craniocerebral injury [ 133 , 134 ].…”
Section: Research On Formulas Containing Both Cinnabar and Realgarmentioning
confidence: 99%